The study of subjective feelings of loneliness older women in terms of suicide risk - Kudryashov E.L.; Lukovtseva Z.V. (Психология и право, 2014)
The results of the study of subjective feeling lonely older women and their actual social status in terms of the propensity to suicidal behavior. Hypothesized that the level of suicide risk in older women reveals a closer connection with the severity of subjective feelings of loneliness than with the degree of objective social isolation. The study involved 52 women aged 55 to 75 years old who do not have mental disorders and debilitating physical illness. The main methods of study was the analysis of medical records, interview and psychological testing formalized. Data used for U-Mann-Whitney test, H-Kruskal-Wallis test, and Pearson criterion 2 Spearman rank correlation method. It is shown that the severity of suicidal risk in the studied sample is really linked to the level of subjective feelings of loneliness (p≤0,05), in respect of the same objective social isolation test found no such relationship.